Melamine tunable effect in a lenalidomide-based supramolecular self-assembly system via hydrogen bonding. (10th July 2017) - Gao, Aiping; Li, Yiran; Lv, Haiting; Liu, Dan; Zhao, Na; Ding, Qianqian; Cao, Xinhua
Abstract : In this study, melamine could tune the self-assembly structures, rheological behaviour, and surface wettability via intermolecular hydrogen bonding between gelator1 and melamine. Abstract : In this study, a new gelator containing lenalidomide and cholesterol groups was synthesized, which could form stable gels in 1, 4-dioxane and mixed solvents of DMF/H2 O (v/v, 1/1). The self-assembly process was studied and certified by field emission scanning electron microscopy, UV-vis, IR, XRD, and CA. Based on the results obtained from the abovementioned analyses, the self-assembly structure, aggregation pattern, and surface wettability could be tuned via the addition of melamine due to intermolecular hydrogen bonding between compound1 and melamine (MA ). The irregular lumpy and the closely packed fiber structures could be turned into microbelt and sparse fiber structures after the addition ofMA, respectively. Moreover, the hydrophobicity of the xerogel film of1-MA was obviously increased. The mechanical strength of gel1-MA was obvisously enhanced due to the addition ofMA . The UV-vis, IR, and XRD experiment results showed that the self-assembly process and mode of1 was changed due to the addition ofMA through intermolecular hydrogen bonding between1 andMA . Therefore, these results provide a method for the regulation of the self-assembly process via intermolecular noncovalent interaction.